Demographic analysis of mass-reared Anastrepha fraterculus (Diptera: Tephritidae) in Tucumán, Argentina Análisis demográfico de la cría masiva de Anastrepha fraterculus (Diptera: Tephritidae) en Tucumán, Argentina - Héctor E. Jaldo; Eduardo Willink; Pablo Liedo (Revista Industrial y Agrícola de Tucumán, 2007)
The life cycle of a lab-adapted mass reared strain of Anastrepha fraterculus at 24°C constant temperature was 41 days, including the preoviposition period. Mortality rates of 8%, 22%, 22%, 5%, and 43% were recorded for eggs, larvae, pupae, adults (preoviposition stage) and adults (reproductive stage), respectively. The intrinsic rate of increase was 0.065, the net fecundity rate was 120.4, and the gross fecundity rate was 328.4. In a stable population, 22% would be eggs, 53% larvae, 18% pupae, 4% preoviposition adults, and 3% reproductive adults. El ciclo de vida de Anastrepha fraterculus en cría masiva a temperatura constante de 24°C fue de 41 días, incluyendo el período de preoviposición. Las mortalidades para huevo, larva, pupa, adultos en preoviposición y adultos reproductivos fueron de 8%, 22%, 22%, 5% y 43%, respectivamente. La tasa intrínseca de incremento natural fue de 0,065, la tasa de fertilidad neta fue de 120,4, y la tasa de fertilidad bruta fue de 328,4. En una población estable 22% debería ser huevos, 53% larvas, 18% pupas, 4% adultos en preoviposición y 3% adultos en etapa reproductiva.